KARAKTERISASI TOKOH ELINA PADA NOVEL â€œICH SPÃœR MICH NICHTâ€KARYA JANA FREY - PRASTIKA, LIA (IDENTITAET, 2016)
To find a literary work, the reader should know how to characterize these figures. Characterization is an attempt toshow the character or the character of the character played. The personality of a fictional character is a behavior of thefictional character that is described by a writer in his or her literature. The personality of fictional character is somethinginevitable from a literature because a reader will not enjoy a literature without a character. The goals of this researchare: (1) Find Elina’s characterization from “Ich spür mich nicht” by Jana Frey. There is one research problem in thisthesis : (1) How is Elina’s characterization from “Ich spür mich nicht” by Jana Frey? This research method isdescriptive qualitative. The data was analyzed through characterizations method by Sayuti und to analyze thecharacterization is introvert or extrovert using the theory of Carl Gustav Jung. The results of this research are: (1)Characterization of Elina in the novel "Ich Spür mich nicht" by Jana Frey in terms of personality psychology of CarlGustav Jung, the leader Elina is likely to have an introverted personality because it has four characteristics introvertpersonality, among other things (a) prefer to be alone, (b) have their own way to express something, (c) is not easy toget along with others, (d) a fanciful or fantasy, and only the personality traits of extravert is confident.